Integrating Clinical Laboratory Services, Nursing Departments, And Health Information Systems For Improved Patient Outcomes: A Systematic Review Of Collaborative Care Models (The Review of Diabetic Studies, 2025)
The integration of Clinical Laboratory Services, Nursing Departments, and interoperability-enabled Health Information Systems is increasingly recognized as a strategic determinant of patient-centered outcomes. Despite technological advances in Laboratory Diagnostics and the critical influence of frontline Nursing Professionals, fragmented digital documentation and non-interoperable data workflows continue to generate diagnostic delays, elevated error rates, and compromised care continuity, particularly in complex clinical environments. This systematic review conceptually evaluates evidence-based collaborative care models, guided by the standardized reporting structure of the PRISMA to assess the clinical effectiveness of integrated workflows on error reduction, diagnostic turnaround time, information accuracy, and patient safety outcomes. The synthesis emphasizes that cross-departmental alignment through shared clinical data exchange, governance-led process design, and harmonized documentation protocols contributes to measurable improvement in patient outcomes, strengthened safety culture, reduced operational inefficiencies, and enhanced decision-making quality across clinical cycles. Integration enablers include electronic record interoperability, structured knowledge nodes for reporting, and multidisciplinary workflow synchronization. The review advocates for sustained health system optimization by institutionalizing collaborative laboratory–nursing–information ecosystems to support patient safety, clinical reliability, and continuous performance improvement.